2006
DOI: 10.1080/00016480600606723
|View full text |Cite
|
Sign up to set email alerts
|

Immune-mediated inner ear disease

Abstract: The incidence of autoimmune inner ear disease (AIED) is difficult to determine: probably it is a rare disease, accounting for <1% of all cases of hearing impairment or dizziness. Nevertheless, the diagnosis of AIED might be overlooked because of the lack of a specific diagnostic test. The hallmark of this clinically diagnosed condition is the presence of a rapidly progressive, often fluctuating, bilateral sensorineural hearing loss (SNHL) over a period of weeks to months. The progression of hearing loss is too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
100
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 71 publications
0
100
2
3
Order By: Relevance
“…Sometimes, there is an elevation in the level of C-reactive protein (CRP), but often no alteration in inflammation parameters is observed, therefore, no specific diagnostic test is performed. 2 The results of radiographic studies of CS cases, such as cranial CT and MRI, are often normal; which could be useful in the exclusion of other causes of vestibuloauditory symptoms such as stroke or neoplasm. 5 CS is a cause of progressive deafness; it is assumed to be an ''autoimmune disease''.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, there is an elevation in the level of C-reactive protein (CRP), but often no alteration in inflammation parameters is observed, therefore, no specific diagnostic test is performed. 2 The results of radiographic studies of CS cases, such as cranial CT and MRI, are often normal; which could be useful in the exclusion of other causes of vestibuloauditory symptoms such as stroke or neoplasm. 5 CS is a cause of progressive deafness; it is assumed to be an ''autoimmune disease''.…”
Section: Discussionmentioning
confidence: 99%
“…Type II and III immunological reactions would be causing inner ear pathology together in pediatric CD patients [28,29]. In type II reaction, an immunoglobulin directed against a tissue or organ is basic mechanism for injury of endolymphatic sac as in the pathogenesis of Meniere's disease and in type III reaction an immune complex deposition leads to inner ear pathology as in the pathogenesis of Wegeners granulomatosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many systemic autoimmune diseases are associated with hearing loss (Bovo et al ., 2006) while patients with seemingly isolated sensorineural hearing loss can have autoantibodies against inner ear antigens (Greco et al ., 2011). A comprehensive bioinformatic analysis has revealed that inner ear proteins share sequence similarity with many known immunogenic proteins, which may lead to cross‐reactivity and detrimental immune activation in the inner ear (Platt et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%